Increasing Motivation and Learning Outcomes of Sociology Students Through the Application of Problem Based Learning Model in Class Xi Ips-1 Sma Negeri 4 Bengkulu City - Jumaida, Safrina (UNIVED Press, Universitas Dehasen Bengkulu, 2023)
The main objective of this classroom action research is to determine the increase in student learning outcomes in Sociology learning in class XI IPS-1 SMA Negeri 4 Bengkulu City for the 2022-2023 academic year through the application of the Problem Based Learning learning model in an effort to increase motivation and sociology learning outcomes and to get an overview of the development of Sociology learning in high school by using the application of the Problem Based Learning learning model in an effort to increase motivation and student learning outcomes in improving the quality of the Teaching and Learning Process (PBM) in sociology subjects in class XI IPS-1 SMA Negeri 4 Bengkulu City in lessons 2022-2023. Based on the results of the research, it shows that the application of the Problem Based Learning learning model has a positive impact on improving student learning outcomes. This can be seen from the increasingly solid understanding of students towards sociology material delivered by the teacher, the average value of learning outcomes increases, namely at 69.38 in cycle I , amounting to 77.21 in cycle II and 82.38 in cycle III. While the completeness scores of student learning outcomes in cycle, cycle II, and in cycle III were 58.33%, 79.16% and 100%, respectively. In the third cycle of classical student learning completeness has been achieved. Students' motivation in studying sociology also continues to increase along with the enthusiasm of students who are also increasing.